2007
DOI: 10.1677/joe-07-0102
|View full text |Cite
|
Sign up to set email alerts
|

Lack of vasoactive intestinal peptide reduces testosterone levels and reproductive aging in mouse testis

Abstract: The neuropeptides vasoactive intestinal peptide (VIP) and pituitary adenylate cyclase-activating polypeptide have long been considered as putative regulators of testicular functions. In vitro evidence suggests that VIP could play an important role in testosterone biosynthesis. However, the endogenous role of VIP on testicular functions remained to be demonstrated. In C57BL/6 mice exhibiting a complete disruption of the VIP gene, we first observed here that serum testosterone levels were lower than those of WT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
1
21
1
Order By: Relevance
“…No differences were found between the two genotype (Figure 8; t =−0.60, p=0.55). However, both null and wild-type mice had high variation in blood testosterone levels, this variation was reported previously in other strains of mice [3739]. Since hemolysis, the breakdown of erythrocytes with subsequent release of their intracellular contents, might interfere with the test results [40], we repeated the experiment using the BD Vacutainer® SST™ serum separation tubes.…”
Section: Resultsmentioning
confidence: 75%
“…No differences were found between the two genotype (Figure 8; t =−0.60, p=0.55). However, both null and wild-type mice had high variation in blood testosterone levels, this variation was reported previously in other strains of mice [3739]. Since hemolysis, the breakdown of erythrocytes with subsequent release of their intracellular contents, might interfere with the test results [40], we repeated the experiment using the BD Vacutainer® SST™ serum separation tubes.…”
Section: Resultsmentioning
confidence: 75%
“…For example, we have shown that targeted mutation of the VIP gene leads to several behavioral and endocrine dysfunctions (17)(18)(19)(20)(21). These mice show inflammation in the lung in basal conditions and airway hyperresponsiveness to methacholine aerosols (20,21), as well as pulmonary artery hypertension, right ventricular hypertrophy, and thickening of the walls of the pulmonary artery and branches (22).…”
mentioning
confidence: 99%
“…Although the VIP−/− female mice also exhibit an advanced phase angle of entrainment, its magnitude is half that of their male counterparts (Table 2), suggesting there is a sex-dependent effect of the mutation. Additional sex-dependent effects include the reduced amount of activity specific to the VIP−/− males, which may be mediated by testosterone, also reduced in VIP−/− males (Lacombe et al, 2007). Physiologically, our data indicates that the VIP−/− females have severe deficits in the expression of daily rhythms in spontaneous electrical activity (Fig.…”
Section: Discussionmentioning
confidence: 99%